2020
DOI: 10.1109/access.2020.2976723
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Prioritization of Agile Requirements Change Management Success Factors in the Domain of Global Software Development

Abstract: The economic and strategic gains motivated the majority of software firms to adopt global software development (GSD). The adoption of GSD is not straightforward. The geographical distance between the GSD teams causes the various problems for the implementation of agile software development activities, particularly, that related to requirements change management in agile (ARCM). The objective of this study is to explore the success factors of ARCM in GSD context and prioritized them based on their significance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
(80 reference statements)
0
20
1
1
Order By: Relevance
“…One possible threat towards the validity of this paper is that, due to the limited time and resources, the sample size of the survey questionnaire ( n = 123) might not be strong enough to justify the validity of the reported factors. However, based on different other existing studies [33, 35, 65, 66 ], this is a representative sample to justify the results and discussion of this study.…”
Section: Limitations Of the Studymentioning
confidence: 90%
“…One possible threat towards the validity of this paper is that, due to the limited time and resources, the sample size of the survey questionnaire ( n = 123) might not be strong enough to justify the validity of the reported factors. However, based on different other existing studies [33, 35, 65, 66 ], this is a representative sample to justify the results and discussion of this study.…”
Section: Limitations Of the Studymentioning
confidence: 90%
“…is model also supports global software development for measuring and improving ARCMRM. Kamal et al [92] identified 21 key success and progress factor of ARCM, and the findings and results show that they are beneficial for practitioners for management of change in global software development context. Moreover, use automated techniques and tools to manage requirement issues, i.e., JIRA and RE-KOMBINE [40,71,87].…”
Section: Tacit Knowledgementioning
confidence: 99%
“…Tacit knowledge [73] Direct communication, observation, surveys, interviews, and the three factors: domain expert, communication process, and audience will help [40] Changing requirements [6,16,40,71,75] Use agile requirement change management readiness model (ARCMRM) [91], adopt 21 progress and success factors of ARCM [92], automated techniques, and tools to manage the requirement issues, i.e., JIRA and RE-KOMBINE [40,71,87] Requirement prioritization [74,77] Four stages based frame has been proposed [93] Negligence of nonfunctional requirements [40] Simulation tool NORMATIC for NFRs modeling [67], planning and visualization procedure, [94], NFR elicitation process [95] Complex software development projects such as supply chain management having unstable and uncertain requirement Long duration of RE due to complex decision making process, difficulty in creating and maintaining requirement priority list…”
Section: Less Preliminary Planning Focus and No Initial Teammentioning
confidence: 99%
“…There were multiple challenges highlighted that are associated with the software requirements including (i) Am-biguous requirements, (ii) Poor requirements definition, (iii) Requirements prioritization, (iv) Requirements changes, (v) Requirements traceability, (vi) Technical solutions, (vii) Requirements verification and validation, and (viii) Project management. Kamal et al [39] reported 21 success factors in agile RCM in GSD. The authors reported that human resource management is an important factor that affects communication and coordination in GSD.…”
Section: Related Workmentioning
confidence: 99%